AutoCAD® 2009 & AutoCAD LT® 2009 bible - Finkelstein, Ellen (Bible (Wiley), 2008)
"This comprehensive guide is your best, one-stop, go-to guide for everything you'll need to master AutoCAD. Whether you're an AutoCAD veteran exploring what's new or a novice seeking to start with the basics and progress to advanced programming, every feature is covered. Start drawing today with the one book you need to succeed with AutoCAD 2009"--Jacket.